2021
DOI: 10.1136/tobaccocontrol-2021-056896
|View full text |Cite
|
Sign up to set email alerts
|

Systemic biomarkers of exposure associated with ENDS use: a scoping review

Abstract: ObjectiveThis scoping review provides an overview of the existing literature on biomarkers of exposure from electronic nicotine delivery systems (ENDS) use and identifies gaps in existing knowledge.Data sourcesWe searched two international databases (PubMed and Web of Science) to identify relevant studies published from August 2013 to February 2021.Data selectionStudies were included if they assessed and compared biomarkers of exposure between exclusive ENDS users, non-users, exclusive cigarette smokers, dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Multiple studies have evaluated biomarkers of carcinogen and toxicant exposure in subjects who used e-cigarettes versus conventional cigarettes or nonusers of any tobacco product, as recently reviewed. The vast majority of these studies have made biomarker measurements at a single time point, or more than one time point over a relatively short duration. Although e-cigarette use consistently resulted in significantly lower exposure to carcinogens and toxicants than cigarette smoking, a few of these single time point studies demonstrated elevated levels of certain biomarkers of volatile toxicants or carcinogens such as acrolein and acrylonitrile in e-cigarette users versus nontobacco users, as summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have evaluated biomarkers of carcinogen and toxicant exposure in subjects who used e-cigarettes versus conventional cigarettes or nonusers of any tobacco product, as recently reviewed. The vast majority of these studies have made biomarker measurements at a single time point, or more than one time point over a relatively short duration. Although e-cigarette use consistently resulted in significantly lower exposure to carcinogens and toxicants than cigarette smoking, a few of these single time point studies demonstrated elevated levels of certain biomarkers of volatile toxicants or carcinogens such as acrolein and acrylonitrile in e-cigarette users versus nontobacco users, as summarized in Table .…”
Section: Introductionmentioning
confidence: 99%
“…19 A recent meta-analysis of biomarkers of ENDS versus cigarettes reported a more favorable biomarker profile of ENDS use, though the last author of the study has been reported to have ties to the tobacco industry. 21,22 Another systematic review also reported reduced levels of some biomarkers in ENDS users relative to current cigarette users, but this is not consistent for all biomarkers (Hiler et al, 2021). 23 By examining the correlation in biomarker profiles for vaping, dual use, and smoking, we observed that the vaping profile is largely distinct from both the dual use and smoking profile which are in turn highly correlated to each other.…”
Section: Discussionmentioning
confidence: 89%
“…21,22 Another systematic review also reported reduced levels of some biomarkers in ENDS users relative to current cigarette users, but this is not consistent for all biomarkers (Hiler et al, 2021). 23 By examining the correlation in biomarker profiles for vaping, dual use, and smoking, we observed that the vaping profile is largely distinct from both the dual use and smoking profile which are in turn highly correlated to each other. We did however observe multiple examples of shared RNA and protein biomarkers between smoking, vaping, and dual use, such as GPR15, a regulator of Linear discrimination analysis models were used to classify vaping and smoking groups.…”
Section: Discussionmentioning
confidence: 89%
“…There is an urgent need for nonnicotine biomarkers of ENDS use to study its long-term effects on health compared to traditional cigarettes. A recent review suggests that many volatile organic compounds and heavy metals are present in both cigarette smokers and ENDS users, but propylene glycol levels may differentiate ENDS users from tobacco smokers (Hiler et al, 2021). Another potential biomarker may be DNA methylation patterns, as some unique methylation patterns have already been linked to combustible tobacco use (Philibert et al, 2013; Reynolds et al, 2015).…”
Section: Discussionmentioning
confidence: 99%